Peran Orang Tua Dalam Implementasi Kurikulum Merdeka Di Kelurahan Laucimba Kecamatan Kabanjahe Kabupaten Karo - Pelista Karo Sekali; Jainab Jainab; Srie Faizah Lisnasari (Jurnal Pengabdian Kepada Masyarakat Digital, 2023)
This community service aims to socialize the Role of Parents in the Implementation of the Independent Curriculum in Laucimba Village, Kabanjahe District, Karo Regency, so that parents have the provision to position themselves so that they can take a role in the success of the Independent Curriculum. The method used in this socialization consists of several stages: the PGSD lecturer team/lecturer: conducts orientation to the village head and parents, conducts lectures on the role of parents in implementing the independent learning curriculum, conducts lectures on the role of parents in implementing the independent learning curriculum, conducts activities program monitoring and evaluation, conducting activity reports. The expected results of this activity, parents do the following: find out what an independent curriculum is, understand what interests and talents are possessed by children, provide support for activities carried out by children while doing assignments or exploring their potential, understanding learning styles children, providing ongoing guidance, establishing communication with the teacher and the child's homeroom teacher. Keyword: role of parents, curriculum, independent learning